2020
DOI: 10.1093/toxsci/kfaa164
|View full text |Cite
|
Sign up to set email alerts
|

Early Gestational Exposure to Inhaled Ozone Impairs Maternal Uterine Artery and Cardiac Function

Abstract: Exposure to air pollutants such as ozone (O3) is associated with adverse pregnancy outcomes, including higher incidence of gestational hypertension, preeclampsia and peripartum cardiomyopathy; however, the underlying mechanisms of this association remain unclear. We hypothesized that O3 exposures during early placental formation would lead to more adverse cardiovascular effects at term for exposed dams, as compared to late-term exposures. Pregnant Sprague-Dawley rats were exposed (4 h) to either filtered air (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“… 35 , 52 Animal experiments showed that the developing placenta was an indirect target of inhaled O 3 and that systemic maternal cardiovascular abnormalities might be induced by O 3 exposure during a specific window of gestation. 53 Pregnant Sprague-Dawley rats exposed to 0.3 ppm of O 3 at gestational day 10 exhibited several late-stage cardiovascular outcomes that were not evident in gestational day 20–exposed dams, including an elevated uterine artery resistance index and reduced cardiac output and stroke volume. 53 One epidemiological study has shown that higher concentrations of O 3 exposure can be a factor in acute vasoconstriction in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 , 52 Animal experiments showed that the developing placenta was an indirect target of inhaled O 3 and that systemic maternal cardiovascular abnormalities might be induced by O 3 exposure during a specific window of gestation. 53 Pregnant Sprague-Dawley rats exposed to 0.3 ppm of O 3 at gestational day 10 exhibited several late-stage cardiovascular outcomes that were not evident in gestational day 20–exposed dams, including an elevated uterine artery resistance index and reduced cardiac output and stroke volume. 53 One epidemiological study has shown that higher concentrations of O 3 exposure can be a factor in acute vasoconstriction in the general population.…”
Section: Discussionmentioning
confidence: 99%
“… 53 Pregnant Sprague-Dawley rats exposed to 0.3 ppm of O 3 at gestational day 10 exhibited several late-stage cardiovascular outcomes that were not evident in gestational day 20–exposed dams, including an elevated uterine artery resistance index and reduced cardiac output and stroke volume. 53 One epidemiological study has shown that higher concentrations of O 3 exposure can be a factor in acute vasoconstriction in the general population. 54 However, due to the physiological changes in pregnant individuals 55 that make them sensitive to air pollution, the mechanism by which O 3 affects blood pressure during pregnancy may be more complex than that in the general population, which requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Although the autonomic sensory innervation and lung-brain neural communication are well studied [147], it is not well understood how the initial irritation induced by air pollutants in the lungs is communicated to the brain in order to induce a neuroendocrine stress response involving ARs and GRs. It has been postulated that bioactive mediators released by the lung cells are responsible for the extrapulmonary and even brain effects of air pollutants [148,149]; however, inflammation takes several hours to occur, but neuroendocrine effects are noted within an hour [85]. Although our studies show that activation of ARs and GRs is required, and that the SAM and HPA axes are stimulated within minutes of ozone exposure, resulting in increased circulating epinephrine and corticosterone, it is important to understand how the initial event induces the neural axes, as well as the role of circulating stress hormones in mediating this event through ARs and GRs.…”
Section: Research Gaps and Opportunitiesmentioning
confidence: 99%
“…Proteomic and phosphoproteomic changes in the cardiac tissue, typi ed by cardiomyopathic ontological classi cations, from pregnant rats exposed to O 3 at GD10.5 were dramatically greater than the changes seen in dams exposed at GD20.5, suggesting that an early impact on placental growth and development may be central to late stage changes. [9] Furthermore, we have observed signi cant alterations of uterine vascular physiology and placental transcription products with late-stage O 3 exposure [13]. Thus, recent preclinical research does indicate a path to gestational hypertension from early-or mid-gestational exposure to air pollution.…”
Section: Introductionmentioning
confidence: 99%